Potencialna raba bukovine in vrednotenje dodane vrednosti v izdelkih iz bukovine - Kropivšek, Jože (Gozdarski vestnik, 2015)
High value added of various wood products as a result of wood processing is crucial for achieving economic efficiency of operations. The study presents potential use of beechwood (Fagus sylvatica L.) and an estimation method for value added of beechwood products. For easier and more transparent study and determination of value added of over 350 so far identified products made of beechwood, 28 groups of products based on technological similarities were suggested. Since the indicator of total value added of product cannot be used for comparison of diverse products (due to different amounts of wood in the material structure of a product as well as due to variety of technological and other requirements of the production), we have developed a model for estimation of value added of beechwood products. In this model, three additional indicators were proposed: (1) total value added per amount of wood used in the product, (2) total value added on share of value of wood used in the product and (3) share of value added in the selling price of the product. The latter is the most important for business decisions. One of the main obstacles to apply the model and evaluate as well as collect the data is to determine the prices of both inputs and outputs. This is closely related to incomparability in determination of the quality of wood in the entire forest-wood chain. Application of the model and identification of problems is presented in detail for the case of sawn wood product.
Keywords: dodana vrednost; vrednotenje; raba lesa; bukovina